2016
DOI: 10.1501/egifak_0000001383
|View full text |Cite
|
Sign up to set email alerts
|

Extremism in education in Pakistan: University teachers’ thoughts

Abstract: This research study was conducted to explore the teachers' thoughts on extremism in education in Pakistan. The idea of research in this aspect was inspired by the recent acts of terrorism in some leading educational institutions of Pakistan. University teachers were interviewed by the researcher. Questions asked by the researcher were developed from the relevant factors taken from respective literature. The researcher validated these questions with the expert opinion of his supervisor. After validation of ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Specifically, for authors like Abdullah and Saeed (2016), Rodríguez (2019) and Sjøen and Mattsson (2020), among others, the teaching of Islamic religion plays a very important role in the educational prevention of violent radicalism. It has been shown that groups like Daesh employ an out-of-context theological narrative that is proving to be very influential, especially among the young (Mansouri and Keskin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for authors like Abdullah and Saeed (2016), Rodríguez (2019) and Sjøen and Mattsson (2020), among others, the teaching of Islamic religion plays a very important role in the educational prevention of violent radicalism. It has been shown that groups like Daesh employ an out-of-context theological narrative that is proving to be very influential, especially among the young (Mansouri and Keskin 2019).…”
Section: Introductionmentioning
confidence: 99%